COVID-AFFECTED LINGUISTIC LANDSCAPE: A CASE OF CITY SIGNS IN PUBLIC PLACES - Irina Tivyaeva; Natalya Chekmaeva (Езиков свят)
The article discusses recent changes to the urban linguistic landscape that were instigated by the spread of the coronavirus infection and expedient public code introduced by city authorities to regulate life in the pandemic-stricken megalopolis. It focuses on relevant signs and images as new entities of the multimodal dialog between the city and its residents. While before 2019 city signs were elements of the city navigation system, the pandemic realities changed their status and role in urban linguistic landscape. The study is based on a dataset of visual records collected across Moscow’s public locations over the years 2020 through 2022. Empirical data are analyzed for their function, language form, and multimodal components. The results suggest that city signs conveying COVID-related messages to city residents perform four major functions: they warn about the virus and health risks, prescribe certain behavioral patterns, motivate to fight the pandemic, and inform about safety measures undertaken by city facilities and businesses. The functional specificity of city signs tends to determine their verbal and non-verbal representation. The study also explores the interplay of visual and verbal components in COVID- affected urban communication and offers insights into new discourse strategies adhered to by the megalopolis when interacting with different social groups in key pandemic moments.